Developing a sonic rain gauge - Tan, Xin Yi (2017)
Current official devices used to measure rain parameters has many limitations. The most common rain device used is a Tipping Bucket Rain Gauge which can only measure rainfall over a period. As a result, a sonic rain gauge was proposed. Rain intensities were indirectly determined using the proposed gauge through individual, distinctive sounds and vibrations produced as raindrops impact the surface of a drumhead. The relationships between raindrop impact force, and sound pressure were determined experimentally under simulated rainfall. Using an audio analyzing software, sound spectrum produced by the sound waves were plotted by Fast Fourier Transform and Standard Autocorrelation analysis. Optimum type of drumhead and sound input setting were also identified. On the basis of these findings, the product underwent its final test in actual rain. Limitations of the proposed gauge were identified as the instrument only showed promising results towards measuring high rainfall rate.